The dawn of detachment: Norbert Elias and sociology's two tracks. (July 2014) - Kilminster, Richard
This article draws on Elias's observations on the origins of political economy and sociology as well as his theory of involvement and detachment to supplement standard accounts of the history of sociology. It shows how, in the 1840s, sociology bifurcated into two tracks. Track I was the highly 'involved' partisan track associated with Marx and Engels and track II was the relatively 'detached', non-partisan track pursued by Saint-Simon, Comte, Lorenz von Stein and others. These two tracks continue to shape contemporary sociology as basic orientations. The polarization of class conflict predicted in Marx's theory is contrasted with the class interdependence model in Lorenz von Stein, in particular. Elias's work is understood as a synthesis of later developments in track II in which he strongly reaffirmed the historical separation of sociology from philosophy. Elias's work is presented as a central theory of society and as a promising alternative to the prevailing practice of theoretical eclecticism in sociology.